Climate change impacts on the watersheds of Lakes Onego and Ladoga from remote sensing and in situ data. Issue 2 (3rd April 2019) - Filatov, Nikolay; Baklagin, Vyacheslav; Efremova, Tatyana; Nazarova, Larisa; Palshin, Nikolay
ABSTRACT: This study investigated climate change impacts on watershed parameters as well as on water balance, water temperatures, and ice-cover regime for 2 large lakes in western Russia, Lakes Ladoga and Onego. Parts of the study occurred during a period of pronounced warming and limited ice cover on Lake Ladoga, which precluded winter surveys of the lake. This limitation notwithstanding, the research provides background climatic and hydrological conditions for the joint Russian–Swiss project "Lake Ladoga – Life under the ice." For both Lakes Onego and Ladoga from 1955 to 2017, air temperature, precipitation, and evaporation data all showed increasing trends, and inflow, outflow, and water levels showed no discernible changes from baseline conditions. Thermal and ice conditions of Lake Onego showed greater sensitivity to climatic changes than corresponding conditions for Lake Ladoga because of the latter's significantly smaller volume and lower heat content. The total ice-cover duration for Lake Onego decreased ∼20 days during the observation period. Detailed data analysis also revealed key characteristics of the Shuya River discharge into Petrozavodsk Bay, where a major part of the fieldwork occurred. River discharge into Lakes Ladoga and Onego increased in the winter. These processes collectively can change the hydrochemical conditions, water quality, and habitat.